Hepatitis C virus reactivation in patients receiving cancer treatment: A prospective observational study. Issue 1 (13th November 2017) - Torres, Harrys A.; Hosry, Jeff; Mahale, Parag; Economides, Minas P.; Jiang, Ying; Lok, Anna S.
Abstract : Hepatitis C virus (HCV) reactivation in patients receiving cancer treatment has been reported in retrospective studies. We sought to determine prospectively the incidence, predictors, and clinical significance of HCV reactivation during cancer treatment. HCV‐infected patients receiving cancer treatment at our institution between November 2012 and July 2016 were studied. Reactivation was defined as an increase in HCV‐RNA ≥1 log10 IU/mL over baseline and hepatitis flare as an increase in alanine aminotransferase to ≥3 times the upper limit of normal. One hundred patients were studied, 50 with hematologic malignancies and 50 with solid tumors. Reactivation occurred in 23 (23%) patients, including 18 (36%) patients with hematologic malignancies and 5 (10%) patients with solid tumors. In univariate analysis, patients with reactivation were more likely than those without reactivation to have prolonged lymphopenia (median, 95 versus 22 days; P = 0.01) and to have received rituximab (44% versus 9%; P < 0.0001), bendamustine (22% versus 0%; P < 0.001), high‐dose steroids (57% versus 21%; P = 0.001), or purine analogs (22% versus 5%; P = 0.02). Rituximab (odds ratio = 9.52; P = 0.001), and high‐dose steroids (odds ratio = 5.05; P = 0.01) retained significance in multivariable analysis. Of the 23 patients with reactivation, 10 (43%) had hepatitis flare. No patient with reactivation experienced liver failure or liver‐related death within 36 weeks after initiation of cancer treatment. Fourteen patients with hepatitis flare, six of whom had reactivation, required discontinuation or dose reduction of cancer treatment. Conclusion: HCV reactivation occurred in 23% of HCV‐infected patients receiving cancer treatment, and most had an unremarkable clinical course. However, reactivation can affect the cancer treatment plan. Our findings suggest that HCV infection should not contraindicate cancer therapy and infected patients should have access to multiple cancer treatments with close monitoring while receiving regimens associated with HCV reactivation. (Hepatology 2018;67:36‐47).